2021
DOI: 10.1002/cpp.2622
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in the treatment of eating disorders

Abstract: Over the last 25 years, virtual reality (VR) has offered innovative solutions for targeting different key symptoms of eating disorders: from craving to negative emotions, from attentional biases to body dissatisfaction. The present narrative review assesses the existing literature in these areas trying to identify their different levels of clinical evidence. Specifically, the review presents four clinical approaches based upon VR and their implications in the treatment of eating disorders: VR cue exposure, VR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 88 publications
(155 reference statements)
0
27
0
2
Order By: Relevance
“…Presently, over 30 randomized control trials support VR exposure therapy (VRET) as an effective treatment for anxiety-related disorders (i.e., phobias, post-traumatic stress disorder (PTSD), panic disorder), with equivalent effect sizes (10) and attrition rates compared to in vivo exposure therapy (11,12). Moreover, there is growing evidence supporting its utility in assessing and treating a broader range of conditions including autism-spectrum disorders, addiction, depression, eating disorders, pain, and psychosis (13,14). The potential benefits of VR are numerous.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, over 30 randomized control trials support VR exposure therapy (VRET) as an effective treatment for anxiety-related disorders (i.e., phobias, post-traumatic stress disorder (PTSD), panic disorder), with equivalent effect sizes (10) and attrition rates compared to in vivo exposure therapy (11,12). Moreover, there is growing evidence supporting its utility in assessing and treating a broader range of conditions including autism-spectrum disorders, addiction, depression, eating disorders, pain, and psychosis (13,14). The potential benefits of VR are numerous.…”
Section: Introductionmentioning
confidence: 99%
“…The VR cue exposure (VR-CE) and VR reference frame shifting (VR-RFS) are two VR-based cognitive behavioral approaches that are often used in the case of eating disorders, but also increasingly for obesity. While the VR-CE targets symptoms like food cravings and food-related anxiety to reduce overeating ( 10 , 11 ), the VR-RFS targets negative memories of the body that are expected to possibly result in eating disorders or obesity to modify disturbances in body self-perception ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been found that people with AN are more susceptible to bodily illusions compared to healthy controls, with enhanced sensitivity for visual manipulations of the body self ( Crucianelli and Filippetti, 2020 ). This led researchers to investigate the beneficial use of IVR to treat eating disorders through the full body illusion ( Riva et al, 2021 ). The visuo-tactile stimulation of the real and virtual body is an effective way to make individuals with AN feel as they own the virtual body, thus allowing the assessment and modification of their body image ( Serino et al, 2019 ).…”
Section: Using Virtual Realities On Social Purpose: How To Foster Social Connection Among the Most Disconnected Individualsmentioning
confidence: 99%